Anti-angiogenic effects of Moringa oleifera silver nanoparticles on endothelial cells: in vitro and ex vivo studies - Rolla Al-Shalabi; Vuanghao Lim; Ibrahim Al-Deeb; Melissa Kilus; Nozlena Abdul Samad (Exploration of Targeted Anti-tumor Therapy)
Aim: Angiogenesis, invasion, and tube formation are critical processes in tumor progression and metastasis. The use of nanoparticles derived from natural products presents a promising approach for targeted cancer therapy. This study evaluates the anti-angiogenic and anti-invasive effects of Moringa oleifera silver nanoparticles (MO-AgNPs) as a therapeutic strategy against these processes. Methods: The anti-angiogenic and anti-invasive activities of MO-AgNPs were investigated using a series of in vitro and ex vivo models. These included the rat aortic ring assay, endothelial tube formation assay, cell invasion assay using endothelial cell lines (Ea.hy926), and a three-dimensional (3D) co-culture spheroid model to simulate tumor microenvironment behavior. Comparisons were made with known inhibitors: quercetin (15.11 μg/mL) and suramin (100 μg/mL). Results: MO-AgNPs at 12 μg/mL significantly inhibited Ea.hy926 cell invasion by 62.10% and significantly suppressed endothelial tube formation, comparable to the effect of quercetin. In the ex vivo aortic ring assay, MO-AgNPs reduced microvessel sprouting by 83.824 ± 0.081%, surpassing the inhibition achieved by suramin. Additionally, in the 3D spheroid model, MO-AgNPs at concentrations of 12 μg/mL and 6 μg/mL, as well as quercetin, significantly reduced spheroid diameter by day 14, indicating suppressed invasive potential and angiogenic support. Conclusions: MO-AgNPs exhibit strong anti-angiogenic and anti-invasive effects across various tumor-relevant models, highlighting their potential as a therapeutic agent against tumor progression and angiogenesis-related diseases. These results support further investigation of MO-AgNPs as a novel nanotherapeutic for cancer treatment.